(untitled) (Innovation & Development in Engineering and Applied Science, 2026)
Retail SMEs in developing markets often face significant operational inefficiencies due to reliance on manual processing. This research addresses the critical problem of excessive transaction times (over 30 minutes) and the lack of automated fiscal compliance at "Men’s Locker Clothing Ec," a retail store in Ecuador. A descriptive-constructive methodology was applied using the Mobile-D agile framework to design and deploy a cross-platform mobile application with electronic invoicing (Flutter + Firebase). The evaluation followed a mixed-methods approach with 81 users. Results demonstrate a high level of user satisfaction, supporting the Technology Acceptance Model (TAM): 97.5% of users affirmed brand identity consistency, and 96.3% found the app easy and intuitive to use. Crucially, the application improved operational efficiency by reducing the average total purchasing workflow time by 74.07%, shifting from over 30 minutes in the traditional physical process to 15–20 minutes in the digital session. This study validates that lightweight agile methodologies and serverless architectures are effective strategies for modernizing retail SMEs.